2023
DOI: 10.3389/fimmu.2023.1099186
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum alleviates LPS-induced acute immune stress in goats by regulating bacterial communities and blood metabolites

Abstract: The mitigation and prevention of acute immune stress are essential for livestock production. Clostridium butyricum (C. butyricum) has shown positive effects in stabilizing intestinal microbiota disorders, improving immune function and inhibiting disease development, but its effects on ruminants are unclear. Therefore, the current trial hypothesized that C. butyricum could improve goats’ immune function and antioxidant capacity by regulating bacterial communities and blood metabolism and effectively alleviating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Numerous in vivo and in vitro studies have confirmed that probiotics can improve the balance of microbes in the intestinal environment, enhance immune function, and benefit intestinal morphology [16][17][18][19][20][21][22]. In all of these studies, Clostridium butyricum (C. butyricum) has been identified as an effective probiotic that promotes animal growth and maintains intestinal barrier function [20,[23][24][25][26][27][28][29]. C. butyricum, also known as Clostridium tyrosine, is a Gram-positive obligate anaerobic bacillus first isolated from pig intestines in 1880 by Prazmowski.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vivo and in vitro studies have confirmed that probiotics can improve the balance of microbes in the intestinal environment, enhance immune function, and benefit intestinal morphology [16][17][18][19][20][21][22]. In all of these studies, Clostridium butyricum (C. butyricum) has been identified as an effective probiotic that promotes animal growth and maintains intestinal barrier function [20,[23][24][25][26][27][28][29]. C. butyricum, also known as Clostridium tyrosine, is a Gram-positive obligate anaerobic bacillus first isolated from pig intestines in 1880 by Prazmowski.…”
Section: Introductionmentioning
confidence: 99%